AN ANALYSIS OF FIGURATIVE LANGUAGE IN MALEFICENT MOVIE - Agnes Meikurniawaty Nehe; Erika Sinambela; Tiar Pasaribu (Sean Institute, 2022)
The purpose of this study to determine the types of figurative language and the most dominant type of figurative language found in the conversation between Maleficent movie actors. This study use theory by Perrine (1997) to classify each types of data. This study use qualitative method to analyzing the data. The data were obtained from the conversation between the actors in the Maleficent movie script. The amount of data based on the several types of figurative language contained in the maleficent movie script was found simile 38 data (39,58%), irony 6 data (6,26%), understatement 4 data (4,16%), symbol 4 data (4,16%), allegory 8 data (8,33 %), paradox 15 data (15,62%) hyperbole 15 data (15,62%) , metonymy 3 data (3,12%), synecdoche 3 data (3,12%). There are total of 96 figurative languages ​​in the maleficent movie script. The most dominant type of figurative language is simile to describe some of the scenes performed by maleficent actors. Keywords : Figurative Language, Semantics Meaning, Movie